Relationship and Interaction between Person and Work Environment Fit Dimensions - Rapuano, Violeta; Valickas, Andrius (Socialiniai tyrimai, 2018)
In the context of permanent changes in labour market it is insufficient to assess the correspondence between an employee and job only in terms of an employee’s skills, knowledge and competencies in respect to job requirements. We should search for a greater variety of common aspects between the individual and the working environment s/he acts in. Organizations want to select employees who will best meet the demands of the job, adapt to training and changes in job demands, and remain loyal and committed to the organization. Prospective employees in their turn are looking for the organizations which make use of their particular abilities and meet their specific needs. Today’s high-performing employees are looking for more than compensation packages and benefits, they are interested in the increase of their value in labour market. Congruence between the employee and his/her working environment is examined by the multidimensional theory of person-environment fit. A number of studies proving the impact of different dimensions of person-environment fit on employees’ attitudes and behaviour have been carried out. It is established that different dimensions of fit are related to employees’ behaviour and attitude benevolent for the organization, such as job satisfaction, organizational commitment, better performance quality, lower turnover of employees, organizational citizenship behaviour, job engagement, and lower job stress indexes. Nevertheless, scientific literature review has demonstrated that some forms of person-environment fit have not comprehensively been explored and there is a shortage of integrated studies on individual forms of person-environment fit, as well as their correlation with other variables. The aim of the research was to examine the relations of selected person-environmental fit dimensions and their connections to certain attitudes of employees. The objectives of the research were as follows: to analyze theoretical aspects of person and profession, organization and job fit conceptions and their relation to the attitudes of employees; to analyze the interconnection of employees’ profession, organization and job fit and their relations to job satisfaction and intentions to quit the job in one of the biggest Lithuanian insurance companies. The research is relevant as insurance market of the country is permanently increasing, the number of loyal and competent employees is insufficient and high rates of turnover are notable. Thus, it is important to study the factors relating to the above described context and to analyze how person-job environment fit relates to the factors important to employees’ turnover. The research was implemented during the period of January – February, 2018. The respondents were 91 employees of the insurance enterprise holding professionally and hierarchically different positions in the organization. The data analysis has revealed that positive relationships exist between all explored dimensions of person-environment fit. Further analysis has demonstrated that with the growing person-profession, personorganization and person-job fit, employee job satisfaction is increasing and thus his/her intent to leave a position is diminishing. The only dimension, i.e. demands-abilities fit, did not correlate with the employee intention to leave. The results of the study have also revealed that links between person-environment fit dimensions and the analyzed employee attitudes are more complex than simple direct links. This research revealed the importance of needs – supplies correspondence in forecasting the attitudes of employees important for the organization, i.e. job satisfaction and intentions to quit the job. Skills, knowledge and competencies’ based correspondence to job requirements which is widely analyzed in previous research and practically applied in the employee selection and recruitment procedures, had no forecasting effect on the employees’ attitudes. These results revealed the satisfaction of employees’ needs in the efforts to retain him/her. Moreover, the results indicated that the satisfaction of employees’ needs better forecast employees job satisfaction than employee-organization fit. The research also revealed the indirect impact of person-profession fit on the attitudes of employees. It became clear that employee-profession fit influences needs-suppliers correspondence which forecasts employees’ attitudes. Thus, insufficient person-profession fit preconditions diminishes the satisfaction of employees’ needs, which in its turn directly predicts job satisfaction and intentions to quit the job. This confirms the assumption that employees’ needs as expressed in the organizational environment highly depend on the employees’ embeddedness in their profession.